Fertility-oriented Female Reproductive Surgery - Darwish, Atef (IntechOpen, 2017)
In modern practice, the role of female reproductive surgery is declining apparently due to the widespread availability of assisted reproductive technology as an attractive option for infertile couples. To be more precise, prevention of female infertility should be the ultimate goal of all obstetricians and gynecologists during operating on females in the reproductive age. This book concentrates on different issues of fertility preservation both in obstetrics and gynecology. Not a matter of kindly or courtesy, but the core of obstetricians and gynecologists' work is to restore normal anatomy and to preserve fertility for all women in the reproductive age.